ANALISIS TAX PLANNING TERHADAP PAJAK PENGHASILAN BADAN UNTUK MENGEFISIENSIKAN BEBAN PAJAK PENGHASILAN BADAN TERUTANG PADA PT WAHANA ELOK LANGGENG LESTARI “WELL” - Esti Kusumowati; Dewi Rejeki (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2020)
The purpose of the research is to do tax planning that must be done by the company in order to streamline the income tax expense and find out the impact that occurs after tax planning. The method of this research is qualitative descriptive method, that is a research by collecting data in accordance with the actual situation and providing an overview and analysis of existing problems. The result of the research shows that PT Wahana Elok Langgeng Lestari “WELL” has implemented tax planning, for some costs that cannot be deducted into deductible costs and comparing the tax expense before and after-tax planning.The conclusion in tax planning on financial statements can help companies to make efficiency and make savings on corporate income tax. Suggestion for companies to make maximum use of tax planning in utilizing tax-saving alternatives without violating tax regulations.